An observer design for active suspension system - Ahmad, Adizul (2005)
The purpose of this project is to construct an active suspension control for a quarter car model subject to excitation from a road profile using an improved sliding mode control with an observer design. The proportional-integral sliding mode was chosen as a control strategy, and the road profile is estimated by using an observer design. The performance of controller will be compared with the LQR controller. There are three parameters to be observed in this study namely, wheel deflection, the body acceleration and the suspension travel. The performance of this controller will be determined by performing computer simulations using the MATLAB and SIMULINK toolbox.